PENGGUNAAN MEDIA AUGMENTED REALITY PADA PEMBELAJARAN PENGANTAR TEKNOLOGI INFORMASI DI UNIVERSITAS ISLAM MAKASSAR - Khaila Ramadhani; Sri Ramadhani; Andi Muh Akbar Saputra (TEKNOS: Jurnal Pendidikan dan Teknologi, 2023)
The use of technology has changed many aspects of human life, including in the world of education. One of the most popular and widely used technologies in learning is augmented reality. (AR). Augmented reality is a technology that allows users to combine the real world with virtual elements, such as images, audio, or video, thus creating a more interactive and in-depth experience. This research uses a qualitative descriptive research approach and check-lists are used as a research tool. Data collection tools that use a likert scale of questions and answers often provide a spectrum of attitudes that range from “very agree” to “very disagree” with the stated facts. This data collection is built on Google Forms and is used to collect information from respondents. Based on research on the application of AR to the teaching of information search techniques, it can be concluded that the use of AR in education triggers students’ interest and makes them enthusiastic about learning, and is necessary for some subjects (such as an introduction to computer architecture) because it helps them visualize abstract concepts. As a result, students will have easier time to access and understand Augmented Reality (AR)-based instruction on the fundamentals of hard-core computing hardware, and educators will have access to a range of more effective teaching tools. Research on the effectiveness of Augmented Reality (AR) in the classroom shows that this method of information delivery has great potential for further study and development; therefore, it is expected that AR will be increasingly used in classrooms in the future, especially at all levels of education.